Immersive learning research from the perspective of its researchers and practitioners: questionnaire validation and early results from a survey on a conceptual framework for the field - Morgado, Leonel (2023)
Immersive learning research is a field of study that emphasizes diversity of scholarship and subject areas. This diversity presents a challenge for understanding the breadth and depth of the field of immersive learning, a challenge that led to the Immersive Learning Research Network’s call for the community of immersive learning researchers to develop a conceptual framework supporting a common understanding of this diverse field - The Immersive Learning Knowledge Tree. However, this structure has not had its underlying assumptions validated by the larger, diverse community of immersive learning researchers and practitioners. Thus, we developed, validated, and disseminated across associations of the field a questionnaire for analyzing the assumptions, structure, and relevance of the Knowledge Tree proposal. Early results point towards overwhelming agreement from the community on the premise that the field of immersive learning research is muddled/fragmented, the current knowledge partially disjointed, specifically among different disciplines (Q3), due to its interdisciplinary nature. There are also strong indications supporting the premise that researchers active in the field of immersive learning research desire to combine their efforts with others.